RUBBER COMPOSITION FOR TIRE TREAD - MIYASAKA KAZUO (2007)
PROBLEM TO BE SOLVED: To provide a rubber composition for a tire tread which reduces the rolling resistance and improves the wet braking performance in a compound for tire tread and which is improved in the vulcanization speed without deteriorating the scorching. SOLUTION: In a formulation system wherein, based on 100 pts.wt. of a styrene-butadiene copolymer rubber or a blend of a styrene-butadiene copolymer rubber and another diene-based rubber, there are formulated 20-120 pts.wt. of silica, 4-12 wt.% of a silane coupling agent to the silica, 0.5-2.5 pts.wt. of a vulcanization accelerator, 0.5-2.5 pts.wt. of sulfur, and 0.1-2.0 pts.wt. of diphenyl guanidine as a secondary vulcanization accelerator, the rubber composition for the tire tread is further formulated with >2.0-7.0 pts.wt. of zinc oxide and 0.05-0.7 pt.wt. of zinc dibenzyl dithiocarbamate and/or 1,6-bis(N, N'-dibenzyl thiocarbamoyl dithio)hexane as an additional secondary vulcanization accelerator. A pneumatic tire using it is also provided. COPYRIGHT: (C)2007,JPO&INPIT